(untitled) (Revista Innova Educación, 2021)
In recent decades an education that develops creative thinking has been promoted. The teacher must design learning strategies that strengthen this ability in students. The objective of this work was to carry out a detailed investigation on creative thinking and the strategies to promote it in this century. The methodology used was the documentary review of articles published from various reliable sources. Concluding that there is a need to stimulate the creative thinking of students to generate different solutions and face situations that arise in the context.